"A New Enterprise in Our History": William Still, Conductor of The Underground Rail Road (1872). (26th November 2020) - Black, Alex W
Abstract: This article presents the formal and material innovations of The Underground Rail Road (1872) and its author and publisher, William Still. Before the Civil War, Still chaired the Philadelphia Vigilance Committee, which assisted hundreds of fugitives from slavery in making their way to freedom. After the Civil War, Still wrote a book based on his records of their stories. The discrimination Black writers and readers experienced from the publishing business convinced Still to start his own. Still's publishing business, like the movement his book documented, was the work of a collective. He called on family members, allies in reform, and friends in Black periodical publishing to produce and distribute the book. Still promoted the book and the business as an extension of the liberation movement. The labors of the fugitives he had helped, and of the booksellers he employed, would stimulate the economic progress, and protect the political and social gains, for which African Americans were striving. Still, a race man and a businessman, proposed a solution to the inequitable production and distribution of Black books. "The time has come, " he declared, "for colored men to be writing books & selling them too."